Arginine-rich peptides and their internalization mechanisms - Futaki, S; Nakase, I; Tadokoro, A; Takeuchi, T; Jones, A T (Biochemical Society transactions, 2007)
As the versatility and use of CPPs (cell-penetrating peptides) as intracellular delivery vectors have been widely accepted, the cellular uptake mechanisms that enable their efficient internalization have become the subject of much interest. Arginine-rich peptides, including HIV-1 Tatp (transactivator of transcription peptide), are regarded as a representative class of CPPs. Evidence suggests that macropinocytosis plays a crucial role in the cellular uptake of these peptides. We have recently shown that treatment of cells with arginine-rich peptides induces activation of Rac protein leading to F-actin (filamentous actin) organization and macropinocytosis. We have also shown that depletion of membrane-associated proteoglycans results in the failure of this signalling pathway, suggesting that membrane-associated proteoglycans may act as a potential receptor for the induction of macropinocytic uptake of arginine-rich peptides. However, when the macropinocytic pathway is inhibited at a low temperature or by cholesterol depletion, these peptides can be internalized by alternative mechanisms, one of which appears to be direct translocation of the peptides through the plasma membrane. This review summarizes the current theories on both endocytic and non-endocytic aspects of internalization of arginine-rich peptides.